2006
DOI: 10.1007/s10558-006-9021-5
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and Rupture Properties of Porcine Aortic Tissue Measured Using Inflation Testing

Abstract: A new inflation test device was developed to study the mechanical properties of aortic tissue. The device was used to measure failure (rupture) strength and to determine the nonlinear, anisotropic elastic properties of porcine thoracic aorta. The tester was designed to stretch initially flat, circular tissue specimens to rupture under uniform biaxial loading. Water was chosen as the pressurizing fluid. Mechanical stretch and radius of curvature during inflation were measured optically in two orthogonal directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 23 publications
5
35
0
Order By: Relevance
“…In order to identify anisotropic hyperelastic material parameters and to quantify the rupture stress of aneurismal aortic tissues, a bulge inflation test (Mohan and Melvin 1983;Hsu et al 1995;Seshaiyer 2001;Marra et al 2006;Brunon et al 2011) is chosen in this study. The bulge inflation test has several advantages compared to a uniaxial tensile test, a simple biaxial tensile test and a pressurized cylinder test.…”
Section: Inflation Testmentioning
confidence: 99%
“…In order to identify anisotropic hyperelastic material parameters and to quantify the rupture stress of aneurismal aortic tissues, a bulge inflation test (Mohan and Melvin 1983;Hsu et al 1995;Seshaiyer 2001;Marra et al 2006;Brunon et al 2011) is chosen in this study. The bulge inflation test has several advantages compared to a uniaxial tensile test, a simple biaxial tensile test and a pressurized cylinder test.…”
Section: Inflation Testmentioning
confidence: 99%
“…When characterizing true membranes, without any residual stretches, this method has been shown to be capable of providing a rapid and accurate estimate of the material parameters of soft tissues, even for nonlinear and anisotropic materials [20,37]. However, this method's accuracy decreases when the tissue thickness and prestretch increase, as shown by the virtual simulations performed in this study (Figure 3).…”
Section: Numerical Feasibilitymentioning
confidence: 80%
“…These equations were initially derived for thin axisymmetric geometries [10,11], however it has been demonstrated that they can closely approximate the stress resultants in geometries that do not necessarily deform axisymmetrically due to material anisotropy [35,36] including anisotropic tissues subjected to inflation testing [19,20,37].…”
Section: Bulge Tests: Initial Estimatementioning
confidence: 99%
See 2 more Smart Citations